Functional Outcome of Monoplaner Exterrnal Fixation for Gustillo Anderson Type III Open Tibia Diaphysis Fractures - Shafi Ul Haq,; Qasim, Muhammad; Khan, Absar; Saeed, Muhammad; Waqar, Muhammad (Indus Journal of Bioscience Research, 2025)
Introduction: Open fracture of tibia is a medical emergency that needs urgent management. Not properly managed open tibia fractures lead to permanent disability or even amputation The reported incidence of open fracture is 2.6% with 40% of which occurring in lower limbs. Tibia diaphysis is a common location for open skeletal fractures as there is scarcity of soft tissue and muscles antero-medially and its anatomy is such that it is more prone to injury.. No protocol and published data is available at our institutions on the management and long term outcome of such fractures. Methodology: This retrospective study has been conducted at Hayatabad Medical teaching institute orthopedic unit. The study duration was 03 years from 1st January 2021 to 31st December 2023 with 02 year follow-up. 215 patients with 226 fractures were included in the study that met the inclusion criteria. There were 147 males and 68 females. Age group of the patient was from 15-60 years. Mean age of the patients was 35.8 years. Results: Functional outcomes were assessed by to John and Wrus criteria 120 patients with type III tibia diaphysis fracture had excellent outcome, 72 out of 226 fractures had good outcome, 29 fractures resulted in fair category, 3 in poor and 2 resulted in amputation of the limb. Conclusion: The study results suggested that Bone healing and soft tissue healing time were strongly correlated with the functional outcome of open tibia diaphysis fracture. Mean bone healing time was 14 weeks.